Residual stress effect on fatigue striation spacing in a cold-worked rivet hole - Matos, P. F. P. de (2004)
The residual stress effect due to cold-working is studied in relation to fatigue striation spacing. Cold-working introduces a compressive stress field around the hole reducing the tendency for fatigue cracks to initiate and grow under cyclic mechanical loading. It is known that fatigue lifetime assessment requires a detailed knowledge of the residual stress profile. X-ray diffraction and 3D finite element analysis (FEA) can be used to determine the residual stress profile. Scanning electron microscopy (SEM) measurements were performed for measuring the striation spacing.